Specification for unplasticized PVC soil and ventilating pipe, fittings and accessories - British Standards Institution (London BSI, 1969)
Unplasticized polyvinyl chloride, Polyvinyl chloride, Polymers, Plastics, Soil stacks, Vent pipes, Stacks, Drainage, Rainwater pipes, Pipes, Pipe fittings, Design, Dimensions, Colour, Spigot-and-socket joints, Softening point, Tensile strength, Marking, Elongation at fracture, Testing conditions, Corrosion tests, Impact testing, Pressure testing, Thermal-cycling tests, Test equipment, Hydraulic tests
Revised, Withdrawn
Cross References BS 1213, BS 2494, BS 2782:Part 0, BS 2782:Part 1:Methods 120A to 120E, BS 2782:Part 3:Methods 320A to 320F, BS 2782:Part 5:Method 540A, BS 2782:Part 11:Method 1101A, BS 2782:Part 11:Method 1102A, BS 2782:Part 11:Method 1102B, BS 2782:Part 11:Method 1103A, BS 4901, BS 5503:Part 1, BS 5504:Part 1, BS 5503:Part 2, BS 5572, BS 5504:Part 2, BS 5627, BS 6209, BS 5504:Part 3, Health and Safety at Work etc. Act 1974
Replaced By BS EN 1329-1:2000, BS 4514:2001
Keywords: Unplasticized polyvinyl chloride -- Standards